P17 The burden of ICS/LABA-treated asthma patients in the UK adult population. (14th November 2013) - Price, D; Mathieson, N; Mulgirigama, A; Scowcroft, A; Pedersini, R; Isherwood, G; Pavord, ID
Abstract : Objectives: According to NHS QOF (Quality and Outcomes Framework) figures, 3.3 million UK citizens have asthma. Previous studies have shown an association of asthma with increased direct and indirect healthcare costs, but similar studies have not been conducted specifically for UK asthma patients. The aim of the current study is to assess the impact of poor asthma control on UK patients treated with ICS + LABA maintenance treatment. Methods: Data were from the 2010 and 2011 UK National Health and Wellness Survey (NHWS), an Internet-based questionnaire from a representative sample of UK adults stratified by age and gender. 701 respondents self-reported a diagnosis of asthma without concomitant COPD, chronic bronchitis, or emphysema and were currently being treated with ICS + LABA. Patients Not Well Controlled (NWC) according to ACT (score < 20) were compared to well-controlled (WC) patients (score ≥ 20) on demographics, medications, health status, BMI, comorbidities, adherence (MMAS-4), healthcare use (number of physician visits, emergency visits and hospitalizations), work productivity and activity impairment (WPAI) and health-related quality of life (HR-QoL) (SF-12). Results: A greater proportion of the 452 NWC patients (64% of the overall sample) go to emergency (21% vs. 14%, p = 0.016) or are hospitalised (13% vs. 8%, p = 0.022), in comparison with the WC; Their mental and physical HR-QoL is lower (SF-12 MCS: 43 vs. 47/100; PCS: 40 vs. 48/100; Health utility: 0.65 vs. 0.74/1.00; all p's < 0.001);while their work and activity impairment are greater: presenteeism (23% vs. 11%, p < 0.001), overall work impairment (29% vs. 17%, p < 0.001) and activity impairment (46% vs. 24%, p < 0.001). In the current sample, NWC did not show significantly different levels of adherence from WC (50% vs. 55%, p = 0.361). Conclusions: Over 60% UK ICS + LABA-treated adult patients are poorly controlled. Poor control is associated with lower HR-QoL, greater healthcare use and productivity impairment, but not with significantly different levels of adherence to WC patients. The recognition of patients remaining symptomatic and utilising healthcare resource whilst treated with ICS + LABA maintenance therapy is an important step to improving their management.